REGISTRY APPLICATION OF GOODS AND STOCK SALES IN WHOLESALE STORES USING THE MICROSOFT VISUAL BASIC 6.0 - Yogo Bhakti Prabowo; Eriek Orlando, SKom, MMSI (Jurnal Sistem Informasi, 2007)
In this scientific writing authors describe the design of the recording applicationprograms and the sale of stock of goods to grocery stores using Microsoft VisualBasic 6.0. In this application program consists of 11 Form. And use the Data AccessObject program to connect to the database. And using Microsoft Access 2003 for itsdatabase.